2016
DOI: 10.3348/kjr.2016.17.2.230
|View full text |Cite
|
Sign up to set email alerts
|

Plug-Assisted Retrograde Transvenous Obliteration for the Treatment of Gastric Variceal Hemorrhage

Abstract: ObjectiveTo evaluate the feasibility, safety, and clinical outcomes of plug-assisted retrograde transvenous obliteration (PARTO) to treat gastric variceal hemorrhage in patients with portal hypertension.Materials and MethodsFrom May 2012 to June 2014, 19 patients (11 men and 8 women, median age; 61, with history of gastric variceal hemorrhage; 17, active bleeding; 2) who underwent PARTO using a vascular plug and a gelfoam pledget were retrospectively analyzed. Clinical and laboratory data were examined to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 29 publications
0
46
0
1
Order By: Relevance
“…For BRTO, PARTO, and CARTO, this ranges from 79 to 100%, 94.7 to 100%, and 100%, respectively. 2,4,5,[27][28][29]31,38,39 In a recent retrospective study comparing BRTO and PARTO, Kim et al reported similar technical success rates of BRTO with EO (93.9%) or STS (92%), and PARTO with Gelfoam (100%). 31 Notably, the success rate of BRTO increases from 84-98% to 98-100% when used in conjunction with balloon-occluded antegrade transvenous obliteration (BATO), although combination therapies are beyond the scope of this article.…”
Section: Outcomes Technical Successmentioning
confidence: 92%
See 4 more Smart Citations
“…For BRTO, PARTO, and CARTO, this ranges from 79 to 100%, 94.7 to 100%, and 100%, respectively. 2,4,5,[27][28][29]31,38,39 In a recent retrospective study comparing BRTO and PARTO, Kim et al reported similar technical success rates of BRTO with EO (93.9%) or STS (92%), and PARTO with Gelfoam (100%). 31 Notably, the success rate of BRTO increases from 84-98% to 98-100% when used in conjunction with balloon-occluded antegrade transvenous obliteration (BATO), although combination therapies are beyond the scope of this article.…”
Section: Outcomes Technical Successmentioning
confidence: 92%
“…AVPII sizes range from 3 to 22 mm, and a plug 20 to 30% larger than the narrowest point of the varix near the left renal vein is selected to avoid migration. 4,[27][28][29] If subsequent contrast injection through the upstream catheter demonstrates inadequate occlusion, with continued portosystemic flow into the left renal vein, small volume Gelfoam embolization, or waiting for 5 to 10 minutes, will achieve stasis. 28 With contrast stasis in the shunt, Gelfoam embolization is performed through the catheter, upstream to the plug, with same end point as BRTO.…”
Section: Balloon-occluded Retrograde Transvenous Obliterationmentioning
confidence: 99%
See 3 more Smart Citations